Damage and Fracture Mechanics Failure Analysis of Engineering Materials and Structures - Boukharouba, Taoufik; Elboujdaini, Mimoun; Pluvinage, Guy (Springer Netherlands : Imprint: Springer, 2009)
The proceedings of the AIQ-ICF conference is a collection of papers on recent advances in methods and approaches to Damage Control and Fracture Mechanics. Written by leading international experts in the area, this book presents new ideas in the field at the highest level and will promote technology transfer and be a key reference for researchers in industry and academia. Subjects cover the broad field of materials properties and performance, including computational approaches to engineering and modelling, materials for energy applications, nanomaterials, biomaterials/biomechanics, pipeline materials, stress corrosion cracking and hydrogen embrittlement, design and construction in joininglwelds, high strength steel (XI00 and higher), fracture mechanics, structural reliability, failure analysis, fatigue, environmentally assisted cracking, fracture dynamics, polymers and composites, and reinforced concrete.